Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Leucaena sp recombinant cinnamyl alcohol dehydrogenase: purification and physicochemical characterization - Patel, Parth; Gupta, Neha; Gaikwad, Sushama M.; Agrawal, Dinesh C.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2014)
Cinnamyl alcohol dehydrogenase is a broad substrate specificity enzyme catalyzing the final step in monolignol biosynthesis, leading to lignin formation in plants. Here, we report characterization of a recombinant CAD homologue (LICAD2) isolated from Leucaena leucocephala. LICAD2 is 80 kDa homodimer associated with non-covalent interactions, having substrate preference toward sinapaldehyde with K-cat/K-m of 11.6 x 10(6) (M-1 s(-1)), and a possible involvement of histidine at the active site. The enzyme remains stable up to 40 C, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 0.002 and 5 h, respectively. LICAD2 showed optimal activity at pH 6.5 and 9 for reduction and oxidation reactions, respectively, and was stable between pH 7 and 9, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 7.5 x 10(-4) and 15 h, respectively. It is a Zn-metalloenzyme with 4 Zn2+ per dimer, however, was inhibited in presence of externally supplemented Zn2+ ions. The enzyme was resistant to osmolytes, reducing agents and non-ionic detergents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cinnamyl alcohol dehydrogenase (CAD); Metalloenzyme; Substrate specificity

Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.

Engineering and in vitro evaluation of acid labile cholesterol tethered MG132 nanoparticle fortargeting ubiquitin-proteasome system in cancer - Ghosh, Chandramouli; Gupta, Neha; More, Piyush; Sengupta, Poulomi; Mallick, Abhik; Santra, Manas Kumar; Basu, Sudipta (Chemistryselect, 2016)
In recent years, proteasome has evolved as one of the important alternative targets in cancer chemotherapy. However, selective targeting of proteasome system in cancer cells still remains a major challenge. To address this, a potent peptide based proteasome inhibitor MG132 was chemically conjugated with biocompatible-biodegradable cholesterol by acid cleavable hydrazone linkage. Spherical nanoparticles (MG132-NPs) were engineered from cholesterol-MG132 conjugate. Increased amount of free MG132 was released from these nanoparticles in acidic environment compared to physiological milieu in a slow and controlled manner. These MG132-NPs were taken up by breast cancer MCF7 cells into lysosomes within 6 h. Proteasome system was inhibited by these MG132-NPs leading to stabilization of beta-catenin, cyclin A and cyclin B in HEK-293T cells. Interestingly, MG132-NPs induced much improved cell death in drug resistant MDA-MB-231 cells with insignificant toxicity in healthy cells (HEK293 and L929) even in higher concentration.

Anticancer activity of lectins from bauhinia purpurea and wisteria floribunda on breast cancer MCF-7 cell lines - Agrawal, Sanskruthi B.; Gupta, Neha; Bhagyawant, Sameer S.; Gaikwad, Sushama M. (Protein and Peptide Letters, 2020)
Background: Individual and collaborative efforts are being made worldwide in search of effective chemical or natural drugs with less severe side-effects for treatment of cancer. Due to the specificity and selectivity properties of lectins for saccharides, several plant lectins are known to induce cytotoxicity into tumor cells. Objective: To study the antiproliferative activity of two N-acetyl galactosamine specific plant lectins from seeds of Bauhinia purpurea and Wisteria floribunda against MCF-7 Breast cancer cell lines. Methods: MTT, lactate dehydrogenase (LDH) leakage, reactive oxygen species (ROS), and caspase-3 assays and flow cytometry for cell cycle analysis were performed. Results: The agglutinins BPL and WFL; 446 mu gml(-1) (2.2 mu M) and 329 mu gml(-1) (2.8 mu M), respectively caused remarkable concentration-dependent antiproliferative effect on MCF-7. The effect was seen to be a consequence of binding of the lectin to the cell surface and triggering S and G2 phase arrest. Apoptosis induced was found to be associated with LDH leakage, cell cycle arrest and ROS generation. The apoptotic signal was observed to be amplified by activation of caspase-3 resulting in cell death. Conclusion: The study provides a base for detailed investigation and further use of lectins in cancer studies.
Keywords: anti-cancer; antiproliferative; Apoptosis; caspase-3; cell cycle arrest; Lectins; MCF-7; reactive oxygen species